Surfactant Free Synthesis of Ag+ Additive Added ZnO Nanostructures - Ramu1, P.; Anbarasan2, P.M.; Aravindan1, S.; Ramesh3, R.; Ponnusamy3, S.; Muthamizhchelvan3, C. (Asian Journal of Chemistry, 2013)
In the present work, pure and additives incorporated nano-ZnO were prepared and their morphological and optical properties were studied. The elemental compositions have been determined using energy dispersive X-ray analysis. Herein, we report a simple method to produce Ag+ additive added ZnO nanostructures. The crystalline phase of the samples was identified as hexagonal wurtzite using X-ray diffraction (XRD). The effect of concentration of Ag+ on morphology of ZnO nanostructures has been investigated using scanning electron microscope (SEM). The formation of ZnO nano flakes is due to selective adsorption of cationic Ag+ on certain crystallographic facets. The optical studies have been carried out using UV-VIS spectrophotometer. These results confirmed that wet-chemical process is comparatively best to produce high yield of ZnO with desired properties at nanometer scale.